Cutaneous plasmablastic plasmacytoma: A case report with literature review - AlHusain , Khalid M.; AlHemli, Haya A.; Bukhari , Meshal A.; Al-Faraidy , Nadya A.; Shaikh, Lenah Y.; AlRabeh , Reem; AlGarni , Ayed (Acta Biomedica Atenei Parmensis, 2025)
Multiple myeloma (MM) is a hematologic malignancy often involving bone marrow and osteolytic lesions. Cutaneous involvement in MM is rare and typically signifies advanced disease. Here, we present a rare case of MM with cutaneous involvement and provide an updated review of the literature on this unusual dermatologic presentation as latest comprehensive review on cutaneous plasmacytoma dates back to 2003. A 50-year-old male with sacral plasmacytoma and elevated immunoglobulin G (IgG) was diagnosed with IgG Kappa MM, ISS stage II. After receiving radiation, chemotherapy, and stem cell transplantation, he achieved a very good partial response and began maintenance therapy with bortezomib-dexamethasone. Three years post-diagnosis, he developed biopsy-confirmed cutaneous plasmacytomas. A retrospective review of case series and reports from 2003 to 2024 using PubMed database identified 11 publications encompassing 27 patients. Our review found that IgG was the most common immunoglobulin subtype in cutaneous plasmacytoma (11/27), primarily affecting older males (15/27) (median age 73). Clinically, nodular lesions (17/27) were the most frequent presentation, predominantly located on the chest area (7/27). Histologically, plasmacytic cellular morphology (12/27) and plasmablastic morphology (11/27) were nearly equally prevalent. Prognosis varied from days to four years post-diagnosis. Despite numerous case reports, significant gaps remain in our understanding of cutaneous plasmacytoma, its risk factors, and clinical associations. Further research should prioritize prospective studies with larger, more diverse cohorts to enhance comprehension of the disease, improve diagnostic accuracy, refine treatment approaches, and ultimately improve patient outcomes.